Crystallographic Characterization of a Fully Rotated, Basic Diiron Dithiolate: Model for the Hred State?. Issue 46 (15th October 2013) - Wang, Wenguang; Rauchfuss, Thomas B.; Moore, Curtis E.; Rheingold, Arnold L.; De Gioia, Luca; Zampella, Giuseppe
<x xml:space="preserve">Abstract</x> A lucky break: A combination of steric pressure and electron asymmetry has provided the first example of a diiron dithiolate that is both rotated and basic. The present work establishes the feasibility of a hydride free rotated structure for the Hred state of the enzyme (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>